Lineage trajectories and fate determinants of postnatal neural stem cells and ependymal cells in the developing ventricular zone. - Jianqun Zheng; Yawen Chen; Yukun Hu; Yujian Zhu; Jie Lin; Manlin Xu; Yunlong Zhang; Weihong Song; Xi Chen (PLoS Biology)
The ventricular zone (VZ) harbors the largest neurogenic niche in the adult mammalian brain and is consisted of neural stem cells (NSCs) and multiciliated ependymal cells (EPCs). Previous lineage tracing studies showed that both NSCs and EPCs were derived from radial glial cells (RGCs). However, the transcriptomic dynamics and the molecular mechanisms guiding the cell fate commitment during the differentiation remain poorly understood. In this study, we analyzed the developing VZ of mice at single-cell resolution and identified three distinct cellular states of RGCs: bipotent glial progenitor cells (bGPCs), neonatal NSC-neuroblasts (nNSC-NBs) and neonatal EPCs (nEPCs). The differentiation from bGPCs to nNSC-NBs and nEPCs forms a continuous bifurcating trajectory. Analysis along the NSC branch unveiled a novel intermediate state of cells expressing oligodendrocyte precursor cell (OPC) and neuroblast (NB) marker genes simultaneously. Several transcription factors (TFs) were found to be essential for the EPC-lineage differentiation. Notably, we uncovered that TFEB can tune NSC/EPC bifurcation, independent of its canonical function as a master regulator of the lysosome biogenesis. TFEB activation prevents the overproduction of EPCs by cooperating with LHX2 to balance the expressions of many multicilia-related genes while promotes the diﬀerentiation into NSC-NBs. Our results resolve the dynamic repertoire of divergent RGCs during VZ development and offer novel insights into the potential application of TFEB-targeted clinical drugs in VZ-related disorders, such as hydrocephalus and neurodegenerative diseases (NDDs).